Physico-chemical qualities of minimally processed carrot stored under vacuum - Rocha, Ada M. C. N. (2011)
In the last decades, consumers have become more health conscious in their food choices, but they have also less time to prepare healthy meals. Increased consumer interest in fruits and vegetables as healthy foods in association with a modification of lifestyles has accelerated and increased efforts to find potential alternatives to the traditional consumption of fresh fruit and vegetables. This situation opens the possibility for new categories of products that are intended to be presented to foodservice operators conveniently peeled, cored or sliced in prepared packages, with fresh-like quality; they are called minimally processed (MP). The use of vacuum packaging presents a potential alternative to achieve an inhibition of the progress of deterioration of foodstuffs. In this study, the physical qualities of MP carrots (cv. Nantes) stored under refrigeration and in vacuum packaging were evaluated. The beneficial effect of vacuum packaging was noticeable only in the colour, sugar content and phenolic compounds of carrots.